2015
DOI: 10.1002/2014rg000475
|View full text |Cite
|
Sign up to set email alerts
|

A review on regional convection‐permitting climate modeling: Demonstrations, prospects, and challenges

Abstract: Regional climate modeling using convection‐permitting models (CPMs; horizontal grid spacing <4 km) emerges as a promising framework to provide more reliable climate information on regional to local scales compared to traditionally used large‐scale models (LSMs; horizontal grid spacing >10 km). CPMs no longer rely on convection parameterization schemes, which had been identified as a major source of errors and uncertainties in LSMs. Moreover, CPMs allow for a more accurate representation of surface and orograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
967
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,067 publications
(1,093 citation statements)
references
References 377 publications
30
967
1
6
Order By: Relevance
“…GCMs also remain important for providing initial and boundary conditions for RCMs (e.g. Kendon et al, 2010), which now yield kilometre-scale climate simulations (Hohenegger et al, 2008;Kendon et al, 2014;Prein et al, 2015), allowing for convection-permitting simulations crucial for representing, in particular, sub-daily precipitation extremes Kendon et al, 2017) and the soil moistureprecipitation feedback (Hohenegger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…GCMs also remain important for providing initial and boundary conditions for RCMs (e.g. Kendon et al, 2010), which now yield kilometre-scale climate simulations (Hohenegger et al, 2008;Kendon et al, 2014;Prein et al, 2015), allowing for convection-permitting simulations crucial for representing, in particular, sub-daily precipitation extremes Kendon et al, 2017) and the soil moistureprecipitation feedback (Hohenegger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial resolution of these numerical experiments is an important aspect of the successful simulation of regional-scale precipitation (e.g., Sato et al 2008;Prein et al 2015). When computational resources are limited, a spatial resolution of coarser than 10 km is commonly used to obtain the climatological ensemble mean of physical variables, in which case a cumulus parameterization (CP) should be used to represent sub-grid-scale precipitation (e.g., Cruz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When computational resources are limited, a spatial resolution of coarser than 10 km is commonly used to obtain the climatological ensemble mean of physical variables, in which case a cumulus parameterization (CP) should be used to represent sub-grid-scale precipitation (e.g., Cruz et al 2016). In contrast, a microphysical process and a triggering of cloud convection are explicitly calculated in experiments using a fine mesh size (e.g., Prein et al 2015), resulting in an improvement in the thermodynamical processes associated with cumulus convection. A finer mesh size also improves the computation of orographic precipitation because it can resolve the dynamical effect of mountains on heavy precipitation (Leung and Qian 2003;Langhans et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Katragkou et al (2015), Kotlarski et al (2014) and Prein et al (2016). The model configurations for the convection-permitting (3 km grid spacing) simulations in the GAR 15 are based on experiences from previous sensitivity experiments (Suklitsch et al 2011;Awan et al 2011;Prein et al 2013;Prein et al 2015). Our RCMs differ from their coarser resolved counterparts (EURO-CORDEX) insofar that the parametrization for deep-convection has been turned off in the GAR.…”
Section: Study Area and Observation Data 20mentioning
confidence: 99%
“…Two major advantages of CPCSs concerning precipitation extremes are: (1) deep moist convection, which is the most important process in the majority of extreme precipitation events, are physically resolved by the RCM and (2) the representation of orography and surface fields is 20 improved. Multiple studies have already demonstrated the added value of convection-permitting models (CPMs, Prein et al, 2015) in capturing extreme precipitation (e.g., Chan et al 2013;Chan et al, 2014;Meredith et al, 2015;Chan et al, 2017;Zittis et al, 2017). However, there are only a few future projections that use CPCSs (e.g., Prein et al, 2017;Ban et al, 2015;Kendon et al, 2014).…”
mentioning
confidence: 99%